Pendidikan Karakter Berbasis Kearifan Lokal Adat Sunda “Ngalaksa” Tarawangsa di Rancakalong Jawa Barat - Kesuma, Guntur Cahaya (Universitas Islam Negeri Raden Intan Lampung, 2016)
Local wisdom contained in some groups / minorities or indigenous communities in Indonesia contains a lot of cultural values of the nation are still going strong into the identity of the character of their peoples. But on the other hand, the value of local knowledge is often overlooked, because they do not correspond with the development era. In fact, from such wisdom could be promoted noble values which can be used as a model in the development of Indonesian culture. In this case the local wisdom of indigenous Sunda